The role of the gut microbiome in health and disease of adult honey bee workers - Raymann, Kasie (Curr Opin Insect Sci, 2018)
The role of the gut microbiome in animal health has become increasingly evident. Unlike most other insects, honey bees possess a highly conserved and specialized core gut microbiome, which consists of nine bacterial species and is acquired mostly through social transmission. Five of these species are ubiquitous in honey bees and are also present in bumble bees. Recent studies have shown that the bee gut microbiome plays a role in metabolism, immune function, growth and development, and protection against pathogens. Disruption of the gut microbiome has also been shown to have detrimental effects on bee health. Overall, evidence suggests that the gut microbiome plays an important role in bee health and disease.